Local Governance and Local Government Finance - Gatot Heri Djatmika (International Journal of Advanced Science and Technology, 2020)
The rationale of this study is to examine the effect of state governance on performance of local government finance in Indonesia. Local governance implementation was measured by local government transparency, accountability, rule of law, people participation and local government size. Using the secondary data of sixty local governments surveyed by Transparency International Indonesia in 2019, a cross-section regression using the econometrics method of Generalized Least Square (GLS) was applied to examine the effects of each factor on local government financial performance. Results show that enforcement of the rule of law which is proxy by the corruption perception index, and people participation proxy by the number of eligible voters had positive significant impacts on Indonesian local government financial performance. The novelties of the study implies that rule of law enforcement and people participation foster people’s trust to pay taxes and to participate in local government decision making that increasing local government revenue.